A tale of two distances: a study of technological distance, geographic distance and multilocation firms. (8th August 2018) - Wang, Shixiang; Zhao, Minyuan
Abstract: The effects of geographic distance and technological distance on knowledge spillovers have been well acknowledged in the literature, but the two distances were mostly discussed in parallel. Taking advantage of the context of multilocation firms in technology clusters, we consider the joint role of geographic and technological distances by focusing on a salient feature of clusters: firms' concern about knowledge appropriation. Specifically, we analyze how a firm's choice of technological distance from local entities is affected by the competitive environment in the cluster as well as its intra-firm technological structure across clusters. Empirical findings based on the global semiconductors industry support our theory that, with stronger local competition, an innovating entity will increase its technological distance from neighbors to reduce unintended knowledge spillovers. However, the technological distance is smaller when the entity is part of a multilocation firm, has a larger technological distance from other locations within the firm and has stronger intra-firm integration across locations. We argue that these features limit knowledge spillovers and, hence, reduce firms' reliance on technological distance as a strategy for knowledge appropriation.